المفهوم التوحيدي لقداسة الكعبة وللحج - Sultan Mohsen Salam, `Abdulnasser (Afkar: Jurnal Akidah dan Pemikiran Islam, 2012)
The holiness of the Kaaba and the practice of Hajj in Islam opened up to the materialists to cast doubt on this religion by claiming that Islam had been influenced by paganism which existed long before Islam as well as its relation with the environment that evolved at that time. In this issue, the materialists seem to depend on certain conceptions about sanctity which is contradicted to the approach of Tawhidic conception. Hence, this article tried to discuss arguments and counter the doubts and suspicions about that Islam is influenced by the Arabs religion prior to it. The discussion focused on the Tawhidic viewpoint on the aspect of ‘holy' semantically according to Islam and its relationship with the position of the Holy Kaaba and the practice of Hajj among Muslims. The argument put forward on the basis of various historical narrative that confirms the texts of the Qur'an.